Stem volume model adjustment fitting for Populus x canadensis ‘Conti 12’ and ‘Guardi’ in irrigated plantations in Mendoza, Argentina - Mundo, Ignacio A; Rovida-Kojima, Elisa A; Aschero, Valeria (Bosque (Valdivia), 2019)
Despite the extensive literature on model fitting to estimate volume in different tree species and regions of Argentina, the references related to volume equations for Populus spp. in irrigated plantations in the Province of Mendoza are scarce. This information is essential for silvicultural management. The objectives of this study were: 1) to calculate and compare the artificial form factors for Populus x canadensis ‘Conti 12’ and ‘Guardi’ clones growing in irrigated plantations in Uco Valley, Mendoza, 2) to fit and compare different equations of stem volume with bark for these two clones and 3) to evaluate the possibility of using a single function to estimate this parameter in both clones. Seven models previously used on Populus in Argentina were fitted to estimate the total stem volume per tree. The form factors for ‘Conti 12’ and ‘Guardi’ were different between them (0.44 and 0.38, respectively). For both, ‘Conti 12’ and ‘Guardi’, the adjustment of the seven models allowed estimating the total stem volume with bark with a very high and similar degree of precision, although in both situations two models (Schumacher-Hall and a variant of the standard function with constant form factor) highlighted over the rest. The statistics of self-validation, homoscedasticity and parsimony criteria allow favoring the decision for the Schumacher-Hall model adjusted individually for each clone and not as a general expression.